STUDI FENOMENOLOGI PENGGUNAAN INSTAGRAM SEBAGAI MEDIA PEMASARAN ORGANIC COCONUT SUGAR RAINAFA - Helmi Tas`an Wartono; Farida Indriani (Jurnal Akuntansi dan Pajak, 2023)
Instagram is the most popular social media based on the playstore. Specifically, Instagram allows users to share images and videos either publicly or privately, and other users can view, comment and click on the like button on them. In addition, Instagram also has complete supporting features compared to other social media. The purpose of this study is to analyze consumer dissatisfaction with the performance of Instagram CV. Barokah Mandiri's results in marketing Rainafa and to analyze CV's Instagram optimization strategy. Results of Barokah Mandiri as Rainafa's promotional media. This study uses a qualitative phenomenological research method. The primary data source in this study was obtained from in-depth interviews with Rainafa's Instagram followers, while secondary data was data obtained by researchers based on literature studies that were in accordance with the problems studied. Through the results of the research discussed in the previous chapter, it can be concluded that the use of Instagram as a marketing medium for organic coconut sugar rainafa is still not optimal. Dissatisfaction with Rainafa's Instagram performance can be seen from 7 aspects, namely context, content, community, customization, communication, connection and commerce. Keywords: instagram;social media;marketing;organic coconut sugar